(untitled) - Navidi, William Cyrus (Boston, 2006)
Statistics for Engineers and Scientists stands out for its crystal clear presentation of applied statistics. Suitable for a one or two semester course, the book takes a practical approach to methods of statistical modeling and data analysis that are most often used in scientific work.
Keywords: Mathematical statistics,Bootstrap (Statistics),Linear models (Statistics); Simulation methods